Pengembangan Aplikasi Pendataan Komplain Warga Berbasis Android (Studi Kasus : Desa Babadan, Bantul) - Pratama, Khrisna Yudha; Wibowo, Adityo Permana (Rekayasa, 2023)
Complaints are quite an important thing in a village community services, with the submission of complaints, allows community administrators to improve the quality of the village and solve many common problems. A slow response in handling complaints can give a bad image to the village administrators. Babadan Village is one of the villages in Bantul Regency, Yogyakarta. In this village, complaints are sent by the villagers by contacting the head of the village through the social media WhatsApp. However, over time this method is no longer considered effective, and causes a lack of responsiveness in handling complaints. Therefore, through the development of this application, it can hopefully facilitate the villagers in submitting complaints to the administrator and can also make the administrator faster in handling complaint reports from its villagers. The systems planning begins with analyzing the current system, prototyping, testing, and then ends with implementation. Then the development method of android mobile-based applications will be done by applying the RESTful API Technology.  Based on the results given from this study, the application was able to function in line with the objectives that have been described.